Anthroponoses: humans infecting animals with infectious diseases - Clement Meseko; Peace Ochai; Meshach Maina (Academia Biology)
Viruses are transmitted from humans to animals just as they are transmitted from animals to humans. The interspecies transmission barrier between animals and humans with respect to zoonotic pathogens is reducing. This reduction is partly due to the increased intermingling between humans, animals, and biological/environmental factors. The recurring classical H1N1 swine influenza virus, which is circulating even now, is a spillover from the 1918 human influenza pandemic that was introduced into the pig population. Also, most recently, SARS-CoV-2, the causative pathogen of COVID-19, has been retransmitted from humans to animals in a phenomenon described as “reverse zoonoses.” Multidirectional susceptibility to these zoonotic diseases is frequently recorded in humans, companion animals, livestock, zoos, and wildlife. Increase in the occurrence of anthroponoses calls for attention. Therefore, this mini review describes past and recent instances where influenza, coronaviruses, and other pathogens are transmitted from humans to animals. Understanding the threat of zoonoses and anthroponoses underscores the need for a holistic One Health approach for infectious disease control and pandemic preparedness.